2019
DOI: 10.1148/radiol.2018180322
|View full text |Cite
|
Sign up to set email alerts
|

Spot and Diffuse Signs: Quantitative Markers of Intracranial Hematoma Expansion at Dual-Energy CT

Abstract: A fter an intracerebral hemorrhage (ICH), hematoma expansion by 33% or more has been reported in at least 38% of patients within 24 hours after symptom onset (1), and in up to 50% of patients who are on anticoagulation therapy (2). Early hematoma expansion is strongly associated with neurologic deterioration, worse functional outcome, and mortality after ICH (3). Thus, identification of patients at risk for hematoma expansion may help to direct management, in particular with respect to selecting candidates for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…9 Another study used a machine learning approach on DE-CT acquisitions in primary ICH and identified two quantitative markers of HE, which were combined in a HE probability score. The HE probability score showed better accuracy for prediction of HE compared to the conventional SS as assessed on single-energy CT. 9,16 Although this study used an automatic iodine quantification method, while we visually assessed SS, its rationale to use DE-CT for improved detection of SS in predicting HE is likewise.…”
Section: Discussionmentioning
confidence: 99%
“…9 Another study used a machine learning approach on DE-CT acquisitions in primary ICH and identified two quantitative markers of HE, which were combined in a HE probability score. The HE probability score showed better accuracy for prediction of HE compared to the conventional SS as assessed on single-energy CT. 9,16 Although this study used an automatic iodine quantification method, while we visually assessed SS, its rationale to use DE-CT for improved detection of SS in predicting HE is likewise.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study found that incorporating the SpS and other clinical factors into a predictive model could accurately identify patients at high risk of HE and guide treatment decisions ( 54 ). Other studies have explored the use of machine learning algorithms to automatically detect and quantify the spot sign, which may improve the efficiency and accuracy of diagnosis ( 55 , 56 ). Overall, the SpS is a promising imaging marker for predicting the risk of HE in ICH patients, and its accurate detection and quantification may help to guide clinical decision-making and improve patient outcomes.…”
Section: Characteristic Imaging Markers Of Hementioning
confidence: 99%
“…실제 데이터의 경우 이러한 조건부 독립을 만족하지 않는 경우가 많지만, 그럼에도 나이브 베이즈는 좋은 성능을 보인다. 설명변수들의 조건부 독립이라는 가정으로 인해 나이브 베이즈는 분석 대상자 수가 설명 변수의 개수에 비해 많지 않은 경우에도 잘 작동한다( 18 19 ).…”
Section: 문헌 검색을 통한 영상의학 분야의 예측 모형 연구 사례unclassified